Functional diversity vs. monotony: the effect of a multiforage diet as opposed to a single forage diet on animal intake, performance, welfare, and urinary nitrogen excretion. (23rd February 2021) - Garrett, Konagh; Beck, Matt R; Marshall, Cameron J; Fleming, Anita E; Logan, Chris M; Maxwell, Thomas M R; Greer, Andrew W; Gregorini, Pablo
Abstract: The objective of this study was to determine the effect of offering animals a multiforage choice (MF ) of fresh herbages on dry matter intake (DMI ), live weight gain, and animal welfare, in comparison with a monotonous diet of ryegrass ( Lolium perenne L.). Twenty ram lambs (30.5 ± 0.9 kg initial live weight; mean ± SEM), were randomly allocated to either a diet consisting of diverse MF choice or a single forage ryegrass (SF ) diet ( n = 10 per treatment) for 35 d. Both diets were fed ad libitum; however, the MF diet was composed of set dry matter ratios of 24% chicory ( Cichorium intybus L.), 30% lucerne ( Medicago sativa L.), 25% plantain ( Plantago lanceolata L.), and 21% ryegrass. The DMI of the MF lambs was 48% greater ( P < 0.01) and the within animal day-to-day coefficient of variation (CV ) of intake was 26% lower ( P < 0.01) than the SF lambs. The average daily gain (ADG ) of lambs offered the MF diet was 92% greater ( P < 0.01) than the lambs offered the SF diet. The within-animal day-to-day CV of intake was negatively related to ADG ( r = −0.59; P < 0.01). The MF lamb's urinary N concentration was 30% lower ( P < 0.01) than that of the SF lambs. The SF lambs spent more time ( P < 0.05) exhibiting stereotypic behaviors in the afternoon and spent more time observing other animals than the MF. Overall, allocating an MF choice of fresh herbages as opposed to a single forage diet of ryegrass increases DMI and thereby animal performance, while potentially reducing urinary N excretion.